2019
DOI: 10.1523/jneurosci.1922-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARγ Attenuates the Expression of Physical and Affective Nicotine Withdrawal Symptoms through Mechanisms Involving Amygdala and Hippocampus Neurotransmission

Abstract: An isoform of peroxisome proliferator-activated receptors (PPARs), PPAR␥, is the receptor for the thiazolidinedione class of antidiabetic medications including pioglitazone. Neuroanatomical data indicate PPAR␥ localization in brain areas involved in drug addiction. Preclinical and clinical data have shown that pioglitazone reduces alcohol and opioid self-administration, relapse to drug seeking, and plays a role in emotional responses. Here, we investigated the behavioral effect of PPAR␥ manipulation on nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 78 publications
3
24
0
Order By: Relevance
“…Domi et al [ 131 ] investigated the role of PPARγ in anxiety and stress response in mice, showing that its activation prevents the anxiogenic effect of acute stress, while its ablation or the administration of a specific antagonist exacerbates basal anxiety and enhances sensitivity to stress. These results, combined with other studies including preclinical and clinical trials [ 133 , 134 , 135 , 136 , 137 ], demonstrate the therapeutic potential of PPARγ agonists for various neuropsychiatric disorders and drug dependencies. Interestingly, since CBD is a selective PPARγ agonist [ 19 , 138 ], many of its therapeutic effects in alleviating neuropsychiatric disorders could be mediated by PPARγ signaling and by its regulation of the mesolimbic DA activity [ 139 ].…”
Section: Cbd Molecular Targets and Mechanisms Involved In The Neurological And Neuropsychiatric Disorderssupporting
confidence: 66%
“…Domi et al [ 131 ] investigated the role of PPARγ in anxiety and stress response in mice, showing that its activation prevents the anxiogenic effect of acute stress, while its ablation or the administration of a specific antagonist exacerbates basal anxiety and enhances sensitivity to stress. These results, combined with other studies including preclinical and clinical trials [ 133 , 134 , 135 , 136 , 137 ], demonstrate the therapeutic potential of PPARγ agonists for various neuropsychiatric disorders and drug dependencies. Interestingly, since CBD is a selective PPARγ agonist [ 19 , 138 ], many of its therapeutic effects in alleviating neuropsychiatric disorders could be mediated by PPARγ signaling and by its regulation of the mesolimbic DA activity [ 139 ].…”
Section: Cbd Molecular Targets and Mechanisms Involved In The Neurological And Neuropsychiatric Disorderssupporting
confidence: 66%
“…RNAscope in situ hybridization was performed as previously described ( Domi et al, 2019 ; Gavini et al, 2020 ). The RNAscope assay was performed on formalin-fixed, paraffin-embedded (FFPE) tissue.…”
Section: Methodsmentioning
confidence: 99%
“…One recent study found that PPAR-γ activation may play a role in nicotine withdrawal. Administration of pioglitazone prior to assessment of nicotine withdrawal attenuated somatic and anxiety-like signs of withdrawal in rats and in wild-type mice with intact PPAR-γ, but not in conditional neuronal PPAR-γ KO mice [42]. In addition, the effect of pioglitazone on both somatic and anxiety-like signs of nicotine withdrawal was blocked by pre-treatment with the PPAR-γ antagonist GW9662 in WT mice [42].…”
Section: Withdrawal/relapsementioning
confidence: 93%